Kebijakan Sektor Publik, Kontribusi Ekonomi, dan Peran Pemerintah Daerah terhadap Persepsi Penyebab Kerusakan Lingkungan: Studi pada Peserta Kamu Fest 4.0 Kalimantan Tengah 2025 - Elpan Pino’o (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This research aims to analyze the influence of public sector policy, mining economic contribution, and local government roles on youth perceptions regarding the causes of environmental degradation in Central Kalimantan. The respondents were participants of Kamu Fest 4.0 in 2025. Using multiple linear regression analysis and primary survey data, the results show that public policy (X1), economic contribution (X2), and local government roles (X3) simultaneously have a positive effect on youth perceptions of environmental degradation (Y). Partially, public policy (X1) shows a significant effect, local government roles (X3) also show a significant effect, while economic contribution (X2) has a positive but insignificant influence. These findings highlight the importance of effective environmental governance to support sustainability.